ISOLATED CONGENITAL KNEE DISLOCATION: A CASE REPORT - Mesanovic, Edin; Fajic, Fikret; Mesanovic, Amra (Sanamed, 2025)
Introduction: Congenital knee dislocation is a rare orthopedic condition characterized by abnormal positioning of the knee joint at birth, with an estimated incidence of approximately 1 in 100,000 live births. It is often associated with other congenital anomalies, necessitating prompt diagnosis and management. Case Report: A male neonate delivered via cesarean section was referred for orthopedic evaluation due to a left lower extremity deformity. Initial examination revealed left knee hyperextension of approximately -45 degrees and restricted passive flexion limited to 90 degrees. Neurovascular assessment was normal. Radiographic imaging confirmed hyperextension without additional skeletal deformities. The treatment plan involved above-knee cast immobilization in maximal flexion, changed weekly for six weeks. By the end of the immobilization period, the patient exhibited significant improvement, achieving a full passive range of knee flexion and extension. Follow-up two weeks later confirmed normal passive and active ranges of motion, with no residual impairment. Conclusion: Early intervention in congenital knee dislocation is crucial for achieving favorable functional outcomes, emphasizing the effectiveness of non-operative strategies in neonates.